IMPLEMENTATION OF GENRE-BASED APPROACH IN TEACHING WRITING FOR VOCATIONAL HIGH SCHOOL STUDENTS - Purwo Haryono Haryono; Ana Setyandari Setyandari; Virda Auliya Auliya (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2023)
The researchers aimed to describe the implementation of a genre-based approach in writing learning in Vocational High Schools. This research design uses a qualitative descriptive approach. The subject of the study was grade XI students at one of the vocational high schools in Klaten Regency. Data were collected from writing learning events, informants, and some related documents using observation, interview, and documentation techniques. The collected data were analyzed descriptively. The results showed that teachers apply a genre-based approach by following all stages that must be passed, ranging from building knowledge of the field (BkoF), modeling of text (MoT), joint construction of the text (JcoT), to independent construction of the text (IcoT). At the BKoF stage, the teacher introduced the invitation text and built students' knowledge and understanding to reveal the general purpose and type of invitation text. At the MoT stage, the teacher provided examples of unofficial invitation texts to observe and discuss. The teacher facilitated students to name the parts and functions of the sample unofficial invitation text. At the JCoT stage, the teacher divided the class into groups to discuss the text of the unofficial invitation. At the ICoT stage, the teacher asked students individually to create an unofficial invitation text.